The objectives and principles of Islamic governance: perspective of Imam Al-Juwaynī - Suleiman, Hassan; Awang, Abdul Bari; Eletrebi, Mohamed Fathy; Alatas, Alwi (Journal of Islam In Asia International Islamic University Malaysia, 2020)
In a reality of clashing visions and perspectives, vision becomes murky, foundations become shaky, and smoky fumes rule over all. History tends to repeat itself, so after Imam al-Māwardī released his realistic vision justifying Islamic governance in his book Al-Aḥkām al-Ṣulṭāniyyah, Imam al-Juwaynī came out with his own book, Ghiyāth al-Umam fī Tiyāth al-Ẓulam, with a hypothetical mindset, to put in place the foundations and objectives of the shar‘īah for Islamic governance, leadership of the ummah, and strategies to deal with the absence of a mujtahid and leader (imām). Using al-Juwaynī’s book, this research aims to demonstrate his unique contributions to this vast subject, which was, and still is, slippery territory both theoretically and practically. This research uses analytical method to explain the objectives and principles of Islamic governance as explained by Imam al-Juwaynī in Ghiyāth al-Umam within the framework of maqāṣid al-shar‘īah. This study finds that his thought in this field has strong correlation with the concept of maqāṣid al-shar‘īah and can enrich our understanding about Islamic governance.